Experimental Study of the Influence of Teaching Style and Coordination on Learning Outcomes of Jumping Jumping Students of SMP Negeri 12 Bengkulu City - Megi Personi; Dwingki Marta Putra; Dodi Ertanto (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine the effect of teaching style (Inclusion and Practice) and Jumping and Jumping Learning Outcomes. This research was conducted on students of SMP Negeri 12 Bengkulu City, this study used treatment by level 2 x 2. The sample consisted of 40 students who were divided into 4 groups, each consisting of 10 students. The data analysis technique is a two-way analysis of variance (ANOVA) and then continued with the Tukey test at the significance level = .05. The results of this study indicate that (1) the inclusive teaching style has a better effect than the practice teaching style on the Jumping and Jumping Learning Outcomes. (2) There is an interaction between the practice teaching style with the inclusive teaching style and coordination on the Jumping and Jumping Learning Outcomes. (3) The inclusive teaching style has a better effect than the practice teaching style on the Jumping and Jumping Learning Outcomes who have high coordination. (4) The practice teaching style has a better effect than the inclusive teaching style on the Jumping and Jumping Learning Outcomes which have low coordination.